Application of Geospatial Technology for Landslide Risk Mapping Using Weighted Overlay Method in Bogor - Fakhri Reza; Adi Subiyanto; Sutanto Sutanto (CV. Rayyan Dwi Bharata, 2025)
Bogor Regency has a high risk of landslides due to geological factors, steep slopes, high rainfall, and changes in land use. This study analyzes the distribution of landslide risk using a Geographic Information System (GIS) with four main parameters (geology, rainfall, slope, and land use) that are weighted and overlaid using ArcGIS. The results show that the southern part of Bogor, especially Cigudeg, Nanggung, Leuwiliang, and Pamijahan, is at high risk due to a combination of geological and climatic conditions. The resulting landslide risk map provides important input for local governments in spatial planning, land management, and community preparedness. This study highlights the important role of geospatial technology in supporting evidence-based mitigation strategies and sustainable development in disaster-prone areas.